Pengaruh Kualitas Tidur terhadap Tekanan Darah Diastolik sebagai Indikator Dini Risiko Hipertensi pada Mahasiswa - Kurniawan, Hendri; Haryanti, Haryanti (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: High academic demands, intense device use, and irregular lifestyles among college students can impact their sleep quality. Poor sleep quality is suspected to be associated with increased diastolic blood pressure (DDP), which contributes to the risk of long-term hypertension. Objectives: This study aimed to examine the effect of sleep quality on diastolic blood pressure in college students. Methods: The study used a quantitative observational method with a cross-sectional design. The study was conducted at the Occupational Therapy Department of the Health Polytechnic of the Ministry of Health, Surakarta. The study population was first-year undergraduate students of the Applied Occupational Therapy Study Program, with a sample size of 91 people (total sampling). The study variables were measured using the Pittsburgh Sleep Quality Index (PSQI) and a digital sphygmomanometer. Data were analyzed using spearman rank and binary logistic regression using SPSS version 23. Results: The majority of study subjects had normal sleep quality (50,55%) and normal diastolic blood pressure (51,65%). The Spearman rank test results for sleep quality and TDD showed a correlation coefficient (r) of 0,475 with a p-value of 0,008. The binary logistic regression test obtained a coefficient value (B) of 1,128, Exp. (OR) of 3,088 with a p-value of 0,010. Conclusion: Sleep quality significantly affects the increased risk of TDD 3 times higher in students. Keywords: Sleep, Diastolic, Hypertension